In vitro antioxidant enzyme activity and sperm motility at different temperatures in sterlet Acipenser ruthenus and rainbow trout Oncorhynchus mykiss - Dadras, Hadiseh; Dzyuba, Viktoriya; Golpour, Amin; Xin, Miaomiao; Dzyuba, Borys (Fish physiology and biochemistry, 2019)
Influence of in vitro temperature on sperm antioxidant enzyme activity, thiobarbituric acid-reactive substance (TBARS) content and motility parameters was evaluated in sterlet Acipenser ruthenus and rainbow trout Oncorhynchus mykiss. Sperm activation was conducted at 4, 14 and 24 °C in both species. Duration of motility was significantly longer at 4 °C than at 14 and 24 °C in both species. At 60 s post-activation, the velocity of sterlet spermatozoa was highest at 24 °C. This trend continued to 420 s post-activation. In rainbow trout, at 10 s post-activation, the highest velocity was observed at 14 °C. Significantly higher catalase activity was seen at 4 °C in both species. No significant difference in spermatozoon superoxide dismutase activity among temperatures was observed. In sterlet, TBARS content was significantly higher at 24 °C compared to other temperatures, but, in rainbow trout, it was highest at 4 °C. The results presume species-specific level of antioxidant enzyme activity and TBARS content at studied temperatures.
Keywords: Antioxidant enzyme; Oncorhynchus mykiss; spermie; Sperm function; Temperature; Thiobarbituric Acid Reactive Substances; ryby; Sperm Motility; teplota; Superoxide Dismutase; peroxidace lipidů; superoxiddismutasa; Antioxidants; zvířata; Fish; antioxidancia; Fishes; motilita spermií; Male; Spermatozoa; Animals; mužské pohlaví; Lipid Peroxidation; látky reagující s kyselinou thiobarbiturovou